Comprehensive in silico Characterization of Universal Stress Proteins in Rice (Oryza sativa L.) With Insight Into Their Stress-Specific Transcriptional Modulation - Arabia, Shatil; Sami, Asif Ahmed; Akhter, Saima; Sarker, Rakha Hari; Islam, Tahmina (Frontiers in Plant Science, 2021)
In a world where climate change is a reality and its consequences are unprecedented, understanding of the plant adaptive capacity and native stress-responsive machinery is crucial. In recent years, Universal stress proteins (USP) has received much attention in the field of plant science due to their stress-specific transcriptional regulation. This study focuses on the extensive characterization of the USP gene family members in the monocot crop rice (Oryza sativa L. var. japonica). A total of 44 USP genes have been identified in the rice genome. In-silico characterization of these genes showed that domain architecture played a major role in the functional diversification of the USP gene family which holds for all plant USPs. On top of that, a higher conservation of OsUSP members has been exhibited with a monocot genome (Zea mays) as compared to a dicot genome (Arabidopsis thaliana). Expression profiling of the identified genes led to the discovery of multiple OsUSP genes that showed pronounced transcript alteration under various abiotic stress conditions, indicating their potential role as multi-functional stress-specific modules. Furthermore, expression profiling of OsUSP genes using qRT-PCR provided a strong evidence for the utility OsUSP genes in building multi-stress tolerant plant. Altogether, this study leads to suitable USP candidates that could be targeted for plant breeding and genetic engineering experiments to develop stress resilience crop species.